2019
DOI: 10.4103/aer.aer_12_19
|View full text |Cite
|
Sign up to set email alerts
|

Oral pregabalin as premedication on anxiolysis and stress response to laryngoscopy and endotracheal intubation in patients undergoing laparoscopic cholecystectomy: A randomized double-blind study

Abstract: Background: Direct laryngoscopy and tracheal intubation lead to increase in heart rate and blood pressure. This can cause serious complications in patients with coronary artery disease, reactive airways, or intracranial neuropathology. Preoperative anxiety is associated with greater level of postoperative pain. Attenuation of anxiety and hemodynamic response to laryngoscopy and intubation are cornerstone of better anesthetic outcome. Gabapentinoids (gabapentin and pregabalin) have been known to po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Authors showed a significantly lower rate of neuropathic chronic postoperative pain in pregabalin group at 2 and 6 months after surgery. Anxiolytic effect of pregabalin premedication was also demonstrated in recent papers [19,20], but the investigation were not related to spine surgery.…”
Section: Medicine and Dentistrymentioning
confidence: 68%
“…Authors showed a significantly lower rate of neuropathic chronic postoperative pain in pregabalin group at 2 and 6 months after surgery. Anxiolytic effect of pregabalin premedication was also demonstrated in recent papers [19,20], but the investigation were not related to spine surgery.…”
Section: Medicine and Dentistrymentioning
confidence: 68%
“…23 Additionally, melatonin and pregabalin have been used for anxiolysis and to reduce the stress response in rigid laryngoscopy and intubation. 24,25 However, given the relatively short duration of FL-S, even with stroboscopic examination, nonpharmacological strategies such as salt application to the tongue and/or alternative therapies mentioned above in addition to breathing strategies designed to reduce anxiety may be appropriate in most situations and will be targets for future investigations. 3,26 Approaching the multimodal experience of gag and discomfort in a multidisciplinary manner could significantly improve patient experience during FL.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the pregabalin, a structural derivative of the inhibitory neurotransmitter γ aminobutyric acid, possesses analgesic, anticonvulsant, anxiolytic, and sleep modulating activities. Pregabalin binds to α 2 δ subunit of voltage sensitive calcium channels and enhance the release of neurotransmitters at the synapses of primary afferent fibers and second-order sensory neurons (7) . It is cost effective and can be administered orally with peak plasma levels reached within an average interval of 54 minutes (8) .…”
Section: Discussionmentioning
confidence: 99%